2006
DOI: 10.1016/j.neuroimage.2005.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Neural circuits involved in imitation and perspective-taking

Abstract: Is it important to adopt the perspective of the model when learning a new skill? Is the "mirror system" equally involved when the teacher is facing or side-by-side with students? In this functional MRI study, we measured the cerebral hemodynamic changes in participants who watched video-clips depicting simple hand or foot actions. The participants either watched passively or imitated these actions. Half the video-clips depicted actions filmed from the perspective of the participant (1st-person perspective) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
294
1
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(340 citation statements)
references
References 77 publications
36
294
1
5
Order By: Relevance
“…In addition, our results support a neurophysiological advantage for self-related stimuli (Jackson, Meltzoff, & Decety, 2006;Maeda, Kleiner-Fisman, & Pascual-Leone, 2002) as subsequent to IPL-stimulation, -suppression only decreased for the egocentric hands movements. Given that we observed no effect on -suppression during observation of allocentric hands movements subsequent to stimulation, we suggest that other neural mechanisms are involved in the processing of allocentric hands movements.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In addition, our results support a neurophysiological advantage for self-related stimuli (Jackson, Meltzoff, & Decety, 2006;Maeda, Kleiner-Fisman, & Pascual-Leone, 2002) as subsequent to IPL-stimulation, -suppression only decreased for the egocentric hands movements. Given that we observed no effect on -suppression during observation of allocentric hands movements subsequent to stimulation, we suggest that other neural mechanisms are involved in the processing of allocentric hands movements.…”
Section: Discussionsupporting
confidence: 81%
“…Self-other relations have frequently been studied by means of perspectives or viewpoints (e.g. David et al, 2006;Frenkel-Toledo et al, 2013;Jackson et al, 2006;Vogt et al, 2003). Typically, these studies reason that the observation of a movement presented as if the observer is conducting the movement (egocentric) is more self-related than the observation of the movement observed as if facing another agent conducting the movement (allocentric).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging studies have confirmed that a similar system is also present in humans (e.g. Grèzes et al 2003;Buccino et al 2001;Iacoboni et al 1999;Koski et al 2002), and this system has been linked to the automatic imitation of actions by imaging and behavioral studies (e.g., Jackson et al 2006;Leslie et al 2004;Wohlschläger and Bekkering 2002).…”
Section: Introductionmentioning
confidence: 78%
“…Formatted final version available at: http://link.springer.com/article/10.1007%2Fs10339-007-0168-9 cases (e.g. Jackson, Meltzoff, and Decety, 2006) can provide robotics researchers with useful information regarding potential implementation approaches.…”
Section: Perspective Takingmentioning
confidence: 99%